2023
DOI: 10.1002/chem.202301070
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Pressure Sensitive Piezochromic Fluorescence Switching of Tetraphenylethylene‐Anthraquinone

Abstract: Sensing of low-pressure signals is of great importance for cutting-edge technologies. Organic piezochromic molecules offer a promising library of pressure sensitive materials which can be tailor-designed toward specific requirements. However, very few examples of low-pressure sensitive piezochromic fluorescent molecules have been obtained till date, and the underlying mechanisms are still in its infancy. Herein, we report highly sensitive piezochromic fluorescent switching under low-pressure regimes (~60 kPa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As illustrated in Figure 1, our previous study has demonstrated that coumarin-based N-aryl-β-enamino diketone 4 exhibits piezochromic behavior (Figure 1) (Hsieh et al, 2019). We speculate that by linking this pressure-sensitive molecular scaffold (Sagara et al, 2007;Sagara and Kato, 2009;Ma et al, 2015;Naumov et al, 2015;Wang et al, 2015;Li et al, 2021;Wei et al, 2023) of 4 with the present light-sensitive moiety of 7i into one molecule, the resulting hybrid compound may exhibit multistimuli responsive properties in solid state (Zhang et al, 2011;Chiu and Yang, 2020;Vaidya et al, 2021;Martinez-Junquera et al, 2022;Wang et al, 2022). Scheme 3 depicts the conceptual design of the potential dual responsive N-aryl-β-enamino diketone 12.…”
Section: Methodsmentioning
confidence: 80%
“…As illustrated in Figure 1, our previous study has demonstrated that coumarin-based N-aryl-β-enamino diketone 4 exhibits piezochromic behavior (Figure 1) (Hsieh et al, 2019). We speculate that by linking this pressure-sensitive molecular scaffold (Sagara et al, 2007;Sagara and Kato, 2009;Ma et al, 2015;Naumov et al, 2015;Wang et al, 2015;Li et al, 2021;Wei et al, 2023) of 4 with the present light-sensitive moiety of 7i into one molecule, the resulting hybrid compound may exhibit multistimuli responsive properties in solid state (Zhang et al, 2011;Chiu and Yang, 2020;Vaidya et al, 2021;Martinez-Junquera et al, 2022;Wang et al, 2022). Scheme 3 depicts the conceptual design of the potential dual responsive N-aryl-β-enamino diketone 12.…”
Section: Methodsmentioning
confidence: 80%
“…Among the listed stimuli, only the hydrostatic pressure is isotropic stress, generated practically in a diamond anvil cell (DAC), with several GPa usually sufficient to perturb the molecular packings. 36,37 Anisotropic stress testing, such as torsion/tensile, 38,39 shear, and unidirectional compression, 40,41 is also frequently employed for continuous measurements. Sonication, typically employing sound waves with ultrasonic frequencies (>20 kHz), induces cavitation, which has diverse effects, such as disrupting biological tissues and promoting chemical reactions.…”
Section: What Does Deform Materials?mentioning
confidence: 99%
“…The latter operates within a limited time range and transfers as a single or multiple pulsed impact. Among the listed stimuli, only the hydrostatic pressure is isotropic stress, generated practically in a diamond anvil cell (DAC), with several GPa usually sufficient to perturb the molecular packings. , Anisotropic stress testing, such as torsion/tensile, , shear, and unidirectional compression, , is also frequently employed for continuous measurements. Sonication, typically employing sound waves with ultrasonic frequencies (>20 kHz), induces cavitation, which has diverse effects, such as disrupting biological tissues and promoting chemical reactions. , The acoustic radiation force can also generate holographic force fields, allowing 3D manipulation of cells and solid microparticles. Similarly, optical radiation force involves the transfer of momentum carried by the propagation of electromagnetic waves to surfaces or particles. , Light can also generate shockwaves (SW) through a picosecond to femtosecond pulsed lasers, reaching to the order of GPa, , which is 10 5 times greater than the high-velocity impact experiments.…”
Section: Mechanical Stimuli and Luminescencementioning
confidence: 99%
“…26–30 Mechanical pressure can disrupt the supramolecular interactions, molecular conformation and packing that strongly affect the optical bandgap, resulting in the modulation of fluorescence. 31–35 Hence, several π-conjugated organic derivatives have been synthesized and reported for mechanical stimuli-induced reversible fluorescence switching between two fluorescence states (on–on) or change of fluorescence intensity (on–off). 3,36–38…”
Section: Introductionmentioning
confidence: 99%